Anak Sebagai Pelaku Residivis Tindak Pidana Pencurian Dan Perlindungan Hukumnya - Sitti Nurhaliza Musa; Lisnawaty W Badu; Julisa Aprilia Kaluku (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
: The aim of this research is to find out how legal protection is for minors as recidivists of criminal acts of theft and the causal factors in Gorontalo City. The method used is an empirical approach based on field facts, then analyzed descriptively qualitatively. The research results show that legal protection for children who are recidivists is provided during the legal process, starting from the investigation, arrest and detention stages. The legal process is carried out in accordance with the provisions of the SPPA Law, and prioritizes the needs, development and growth of children, both physically, mentally and socially. The implementation of legal protection for children who are in conflict with the law, especially for repeat criminals or recidivists, is carried out in the same way as for first-time perpetrators of other criminal acts, but the only difference is that diversion efforts are not applied to those who are recidivists. The protection carried out by the police is to fulfill children's rights in every ongoing legal process; The investigation prioritizes a family atmosphere; and Separate Detention. The cause of children becoming recidivist perpetrators of the crime of theft in Gorontalo City is environmental factors; Economy problem; There is leniency in punishment and lack of effective coaching; and Factors of legal awareness and parental negligence. Therefore, in implementing legal protection for children who commit criminal acts, especially for recidivist perpetrators, law enforcement officers are expected to pay attention to the psychological and social conditions of children, but still prioritize providing a deterrent effect so that perpetrators are afraid to repeat their crimes. These efforts include, for example, implementing existing legal procedures by fulfilling all children's rights, but still carrying out repressive action by providing sanctions as regulated in statutory regulations, and not imposing diversion on perpetrators who repeat criminal acts. Apart from that, the government and especially parents pay as much attention as possible to ensuring life for children, so that they do not become perpetrators of criminal acts such as theft. This is because children are sometimes forced to commit these crimes due to their needs not being met properly, or even due to pressure from other parties.